Inclusão e cidadania digital no Brasil: a (des) articulação das políticas públicas - Carvalho, Angela Maria Grossi de [UNESP]; Américo, Marcos Tuca [UNESP] (University of Seville, 2014)
The incipient but quickly expansion action on the Information and Communications Technologies (ICT) in Africa it is now just having different impact on these societies. One of these relates bear on how users are identified with these tools. Just like that we find individuals identify as bloggers, twitter followers or cyber activist. This contribution analyzes the Senegal’s fact where a successful use of social nets and web 2.0 tools experience (at least in repercussion) as social and political involvement while presidential elections in 2012 is tied to come back an identity: Cyber activist. Senegalese circumstance shows us how this identity has a personal and assertiveness dimension as well collective aspects of belonging to a community. One as much as the other, show us personal traits in contrast to previous beliefs, basically because it fuse and confuse virtual and reality. Due to dynamics from expanding technology, this identity is youthful and urban, but not only. This situation creates new dynamics at least in this affected group. For this reason, besides knowing emergence and evolution of this fact, it raises some of the involvement in social and political involvement from groups traditionally “invisible”. Beyond the new social behavior there are new changes in the rules of the game in order to start new social revolution.

A mudança da sociedade industrial para a pós-industrial significou uma mudança substancial na importância com novas formas de processamento informacional, novas estruturas e tecnologias. A chamada sociedade da informação vai criando novas possibilidades para os setores econômico, político, cultural e social. No entanto, se percebe novas fronteiras sendo erguidas ao privar a população, em seu todo, de ter acesso e condições de uso das tecnologias da informação e comunicação (TIC) e de toda a estrutura oferecida pelas redes digitais. Refletir sobre essas mudanças e o papel do estado na gestão de políticas públicas que tenham por finalidade a diminuição da brecha digital é o objetivo desse artigo. Por meio de uma metodologia que se utiliza das pesquisas bibliográficas e documental, buscamos demonstrar que as ações governamentais ainda são espaças e insuficientes.
Digital inclusion and citizenship in Brazil: the (dis) articulation of public policies
Keywords: ITC; Social network; Participation; Society; Identity; Sociedade da informação; Inclusão digital; Cidadania digital; Política pública social; Informação e tecnologia